Sugarcane bagasse fiber as semi-reinforcement filler in natural rubber composite sandals - de Paiva, Fábio Friol Guedes [UNESP]; de Maria, Vitor Peixoto Klienchen [UNESP]; Torres, Giovani Barrera; Dognani, Guilherme [UNESP]; dos Santos, Renivaldo José [UNESP]; Cabrera, Flávio Camargo [UNESP]; Job, Aldo Eloizo [UNESP] (Springer Nature, 2019)
In many countries, agricultural wastes cause significant air pollution due owing the burning of large amounts of residue. Biocomposites represent a new generation of materials that are eco-friendly, CO 2 -neutral, economical, low-density and non-petroleum derivatives. They have been widely used to facilitate the reuse of waste and protect the environment. Here, we introduce the reuse of sugarcane bagasse fiber, untreated (SCB U ) and alkaline treated (SCB T ) by incorporation as reinforcement filler in natural rubber composites used in the manufacture of sandals. Composites were prepared using untreated residue and compared with those treated with 10% sodium hydroxide. The alkali treatment allowed to incorporate high amounts of residue without loss of mechanical properties. The alkali treatment decreased 20% of hardness, increased 98% of tensile strength, maintained the flexibility of the rubber composites, increasing elongation at break to 546% (treated) from 303% (untreated), comparing 40 phr of residue. The composite was used in the preparation of sandals adhering to requirements specified in Testing and Research Institute for the Manufacture of Footwear and paves the way for technological innovation in footwear.
Keywords: Biomaterials; Composites; Natural rubber; Sugarcane bagasse; Vulcanization